Nanostructured metal-organic-framework-derived materials for electrochemical energy storage and conversion - Zhang, Songlin (Nanyang Technological University, 2022)
Transition metal-based materials are promising not only in energy storage devices such as batteries, supercapacitors, fuel cells, but also in the field of catalysis. Increasing attention is paid to push the limits of energy storage and conversion by the delicate design of nanomaterials. To this end, metal-organic-frameworks (MOFs) based materials are emerging as outstanding templates and precursors to create nanostructures with various promising functionalities, such as excellent chemical and mechanical stabilities, large specific surface areas, and adjustable pore structures, which are promising for the applications towards energy-related applications. The research work presented in this project focuses on the rational design and synthesis of MOF-derived materials with the desired structure and composition as well as their electrochemical applications. The main results and findings are summarized as follows. 1. Co-Fe alloy@N-doped carbon hollow spheres are designed and synthesized through a dual-MOF-assisted pyrolysis approach for electrocatalytic oxygen reduction reaction (ORR). In this case, dual MOFs shell and polystyrene core are coupled together by one-step encapsulation procedure, enabling the further alloying of metal centers during the pyrolysis stage. After the thermal treatment in N2, the Co-Fe alloy particles originated from the conjunct ZIF-67, and MIL-101 are homogeneously distributed and serve as active sites in porous N-doped carbon nanoshells with nanometer precision. Benefiting from the rich active sites and porous conductive matrix, the catalyst exhibited an enhanced ORR performance with a half-wave potential (E1/2) at 0.854 V. 2. A series of hollow hierarchical nanoplates (NPs) assembled by Co3O4 nanosheets doped with 13 metal atoms are developed through a cooperative etching-coordination-reorganization method for electrocatalytic oxygen evolution reaction (OER). Novel two-dimensional ZIF-67 NPs are synthesized as templates to receive a Lewis acid etching and metal species coordination to form unique cross channels, and thus further converted to hollow Co3O4 hierarchical NPs constructed from ultrathin nanosheet subunits through a controllable solvothermal reaction, during which the metal species are doped into Co3O4 crystal lattice. Benefiting from the structural and compositional advantages, the as-derived Fe-doped Co3O4 hierarchical NPs manifest superior electrocatalytic activity towards OER with an overpotential of 262 mV at 10 mA cm-2, a Tafel slope of 43 mV dec-1, and excellent stability over 50 h at 100 mA cm-2. 3. Ultrafine Pt-Co alloy nanoparticles (sub-10 nm) attached on the inner and outer shells of porous nitrogen-doped carbon nanotubes (NCNT) are synthesized through a MOF-assisted pyrolysis-replacement-reorganization method. During the thermal reorganization, the migration of Pt-Co nano-alloys to both surfaces ensures the maximized exposure of active sites while maintaining the robust attachment to the porous carbon matrix. Density functional theory calculations suggest a nearly thermodynamically-neutral free energy of adsorption of hydrogen intermediates and diversified active sites induced by alloying, thus resulting in a great promotion in intrinsic activity towards the hydrogen evolution reaction (HER). Benefiting from the delicate structural design and compositional modulation, the optimized Pt3Co@NCNT electrocatalyst manifests outstanding HER activity and superior stability in both acidic and alkaline media.